Black aesthetics and the deep ocean - Mohulatsi, Mapule (My University, 2019)
This thesis aims at exploring the ways contemporary black writing has contributed to the imaginaries of the deep ocean. Working with the black aesthetic as well as questions of ocean waste, the thesis looks into the deep ocean as an avenue to think with the aquatic environments emergent future, and past, as well as the ways in which perceptions of the marine environment are influenced in turn. The introduction clearly sets out the rationale of the project, in seeking to complicate simplistic received ideas of black intellectual traditions being cast as nationalistic, territorial or ‘landlocked’ modes, and to draw out the range of cultural, historical and artistic encounters with the sea, as both physical entity and mythic force. The thesis moves from historical analysis (particularly with regard to the mapping of the ocean floor), decolonial studies, feminist epistemologies and cultural / oceanic materialism (in drawing attention to the ‘agentive’ character of the oceans) towards a more fine-grained, open-ended and literary / art-historical mode of interpretation in considering the work of Claudette Schreuder, Neliswe Xaba, Wangechi Mutu, Nalo Hopkinson, Koleka Putuma, Romesh Guneskera and Kei Miller. The thesis treats these various materials sensitively, drawing out their often ambivalent reactions to the ocean with care. At its heart, the project explores the extent to which different cultural mediums (from poetry to visual art to the novel) are able to acknowledge or honour forms of agency where these have often been overlooked or denied by certain kinds of environmentalist, or even postcolonial, discourse.
A Research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts Johannesburg 2019
Keywords: Aesthetics; African American aesthetics